Cerebral metabolism, oxidation and inflammation in severe passive hyperthermia with and without respiratory alkalosis. (11th February 2020) - Bain, Anthony R.; Hoiland, Ryan L.; Donnelly, Joseph; Nowak‐Flück, Daniela; Sekhon, Mypinder; Tymko, Michael M.; Greiner, Jared J.; DeSouza, Christopher A.; Ainslie, Philip N.
Abstract : Key points: It was unknown whether respiratory alkalosis impacts the global cerebral metabolic response as well as the cerebral pro‐oxidation and inflammatory response in passive hyperthermia. This study demonstrated that the cerebral metabolic rate was increased by ∼20% with passive hyperthermia of up to +2°C oesophageal temperature, and this response was unaffected by respiratory alkalosis. Additionally, the increase in cerebral metabolism did not significantly impact the net cerebral release of oxidative and inflammatory markers. These data indicate that passive heating of up to +2°C core temperature in healthy young men is not enough to confer a major oxidative and inflammatory burden on the brain, but it does markedly increase the cerebral metabolic rate, independently of P aC O 2 . Abstract: There is limited information concerning the impact of arterial P C O 2 /pH on heat‐induced alteration in cerebral metabolism, as well as on the cerebral oxidative/inflammatory burden of hyperthermia. Accordingly, we sought to address two hypotheses: (1) passive hyperthermia will increase the cerebral metabolic rate of oxygen (CMRO2 ) consistent with a combined influence of Q10 and respiratory alkalosis; and (2) the net cerebral release of pro‐oxidative and pro‐inflammatory markers will be elevated in hyperthermia, particularly in poikilocapnic hyperthermia. Healthy young men ( n = 6) underwent passive heating until an oesophageal temperature of 2°C above resting was reached. At 0.5°C increments in core temperature, CMRO2 was calculated from the product of cerebral blood flow (ultrasound) and the radial artery–jugular venous oxygen content difference (cannulation). Net cerebral glucose/lactate exchange, and biomarkers of oxidative and inflammatory stress were also measured. At +2.0°C oesophageal temperature, arterial P C O 2 was restored to normothermic values using end‐tidal forcing. The primary findings were: (1) while CMRO2 was increased ( P < 0.05) by ∼20% with hyperthermia of +1.5–2.0°C, this was not influenced by respiratory alkalosis, and (2) although biomarkers of pro‐oxidation and pro‐inflammation were systemically elevated in hyperthermia ( P < 0.05), there were no differences in the trans‐cerebral exchange kinetics. These novel data indicate that passive heating of up to +2°C core temperature in healthy young men is not enough to confer a major oxidative and inflammatory burden on the brain, despite it markedly increasing CMRO2, irrespective of arterial pH. Key points: It was unknown whether respiratory alkalosis impacts the global cerebral metabolic response as well as the cerebral pro‐oxidation and inflammatory response in passive hyperthermia. This study demonstrated that the cerebral metabolic rate was increased by ∼20% with passive hyperthermia of up to +2°C oesophageal temperature, and this response was unaffected by respiratory alkalosis. Additionally, the increase in cerebral metabolism did not significantly impact the net cerebral release of oxidative and inflammatory markers. These data indicate that passive heating of up to +2°C core temperature in healthy young men is not enough to confer a major oxidative and inflammatory burden on the brain, but it does markedly increase the cerebral metabolic rate, independently of P aC O 2 .